2016
DOI: 10.1371/journal.pone.0146746
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in Low-Dose Haloperidol Response for Prevention of Postoperative Nausea and Vomiting: A Register-Based Cohort Study

Abstract: BackgroundPostoperative nausea and vomiting (PONV) is one of the most common and distressing complications after general anesthesia and surgery, with young non-smoking females receiving postoperative opioids being high-risk patients. This register-based study aims to evaluate the effect of low-dose haloperidol (0.5 mg intravenously) directly after induction of general anesthesia to reduce the incidence of PONV in the postoperative anesthesiological care unit (PACU).MethodsMultivariable regression models were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
1
9
0
2
Order By: Relevance
“…Brettner et al . 209 found gender-specific differences in the incidence of PONV (female > males) in the PACU after low-dose haloperidol (0.5 mg IV).…”
Section: Perioperative Antiemetic Drugs Used For the Treatment And/ormentioning
confidence: 81%
See 1 more Smart Citation
“…Brettner et al . 209 found gender-specific differences in the incidence of PONV (female > males) in the PACU after low-dose haloperidol (0.5 mg IV).…”
Section: Perioperative Antiemetic Drugs Used For the Treatment And/ormentioning
confidence: 81%
“…The incidence of QTc prolongation with haloperidol is statistically equivalent to the 5-HT 3 antagonists. Brettner et al 209 found gender-specific differences in the incidence of PONV (female > males) in the PACU after low-dose haloperidol (0.5 mg IV).…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…However, it should be noted that the effect of ondansetron is more than other drugs in most studies. Considering the negative effect of endonestrone on hemodynamic therapy, it is advised to use this drug [ 17 ] [ 19 ] [ 20 ]. The prophylactic use of this drug is recommended in women’s surgery, especially abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…10 )HPDOHV DOVR H[SHULHQFH UHGXFHG EHQH¿FLDO effects from pharmacological prophylaxis. 11 The exact mechanisms responsible for the increased incidence of PONV in females are unknown. Studies have suggested that PONV ULVN LQ IHPDOHV LV LQÀXHQFHG E\ PHQVWUXDO phase, with the highest risk occurring during the follicular phase and lowest risk during the luteal phase.…”
Section: Introductionmentioning
confidence: 99%